Development of the Human Rights in Sports Education Program for the College Student-Athletes - Deockki Hong; Eunju Ham; Jong Mun Cheon (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to develop a sports-related human rights education program for college student-athletes. METHODS To do this, literature reviews, individual interviews, and experts' meeting data were collected. The data were analyzed using content analysis and domain analysis. RESULTS The study involved five steps. First, the literature reviews examined the problems and improvement points regarding previous sports-related human rights education programs. Second, the direction of human rights in sports education programs was developed based on certain development principles and criterion. Third, eight sports-related human rights education lesson plans were developed. Each lesson plan had a format that contained lesson objectives, ice breaking quizzes, core contents, discussion sections, and essential summaries. Fourth, the program was validated using a pilot test. Last, a "human rights in sports" instructor education program was executed. CONCLUSIONS The program can be effectively used among college student-athletes.